Experiences of teaching and learning in K-12 physical education during COVID-19: an international comparative case study. (2nd November 2022) - Howley, Donal
ABSTRACT: Background: The COVID-19 pandemic has led to widespread adaptations and unprecedented realities in the way teaching and learning in physical education (PE) is currently being implemented and experienced globally. Understanding the similarities and differing realities of some of these experiences across contexts and countries can help to inform formal responses going forward to further enhance teaching, learning, and professional development during and beyond this period of time. Purpose: The purpose of this study was to explore teachers' experiences of teaching and learning in K-12 PE settings during COVID-19 across countries. Three research questions guided the study: (1) What realities has the event of COVID-19 brought for teaching and learning for these K-12 PE teachers?, (2) In what ways have these teachers similarly responded to and addressed these realities in their local practice?, and (3) What support mechanisms have these teachers experienced and what additional support do they feel is required? Research design: This qualitative study utilized an international comparative case study design; 10K-12 PE teachers working in a variety of public, private, and alternative education settings in eight countries (Australia, Brazil, China, Ireland, Mexico, New Zealand, South Korea, and the USA) agreed to participate using photovoice and interviews. The Miles and Huberman Framework for Qualitative Data Analysis (1994) was implemented, involving a three/four-step process including data reduction, data display and drawing and verifying conclusions before presenting findings thematically. Findings/discussion: The following thematic findings were constructed from data analysis: figuring out (in)flexibility; personal connection; social and emotional support; looking forward ; and unearthing inequity. The initial impact of COVID-19 led to these teachers across countries collectively transitioning to online remote learning as the standard operating procedure for teaching and learning. The possibility for uniform experiences to occur across contexts was hindered by issues around inequity. Many of the realities and inequities spoken about previously existed such as issues around flexibility in implementing curricula and assessment; narrow and traditional pedagogical approaches to teaching and learning in PE emphasizing physical activity and exercise; establishing a personal connection; a lack of social and emotional support for students; and equitable access. Additionally, the need to provide continued professional development for teachers on how to utilize remote online blended learning and technology is apparent. Conclusion: This study demonstrates how traditional and conventional approaches to teaching and learning in PE fell short while others were adopted, adapted, and enhanced. Further opportunities for teachers to reflect on their experiences of teaching and learning during this time are needed in order to better understand how this period has impacted PE classrooms and what this means for the subject going forward.